Contests and negotiation between hubristic players - Iain W. Long (Cardiff University, Cardiff Business School, 2019)
Why do contests exist in settings where negotiation provides a costless alternative? I assess a new explanation: parties may be overconfident about their ability or optimistic about their chances of winning. For both parties in a contest, this hubris: (i) reduces the incentive to exit the contest; (ii) reduces effort; and(iii) increases expected payoffs. Whilst hubris leads to the contest being preferred to costless negotiation, the welfare loss is nonmonotonic in either behavioural bias.
Keywords: C71; D74; D91; 330; Contests; Optimism bias; Overconfidence bias; Negotiation